2018
DOI: 10.1088/2053-1583/aac055
|View full text |Cite
|
Sign up to set email alerts
|

Electrical percolation in graphene–polymer composites

Abstract: Electrically conductive composites comprising polymers and graphene are extremely versatile and have a wide range of potential applications. The conductivity of these composites depends on the choice of polymer matrix, the type of graphene filler, the processing methodology, and any post-production treatments. In this review, we discuss the progress in graphene–polymer composites for electrical applications. Graphene filler types are reviewed, the progress in modelling these composites is outlined, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
250
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(260 citation statements)
references
References 205 publications
10
250
0
Order By: Relevance
“…[68] Independent follow-up studies demonstrated even larger enhancement in the thermal transport properties of composites at lower loading fractions (≈5 vol%). [87,88] A possibility of preparing composites with graphene loading exceeding the electrical percolation threshold is important for designing the EMI shielding materials. The FLG filler can perform better than SLG filler even though it has lower intrinsic thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[68] Independent follow-up studies demonstrated even larger enhancement in the thermal transport properties of composites at lower loading fractions (≈5 vol%). [87,88] A possibility of preparing composites with graphene loading exceeding the electrical percolation threshold is important for designing the EMI shielding materials. The FLG filler can perform better than SLG filler even though it has lower intrinsic thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters were calculated from the transconductance curves ( I DS ‐ V GS ) (Figures a, S3 and S4) using standard transistor model in saturation regime . The mobility exhibits a characteristic S‐shape dependence on the GNP loading, with a 40x increase with the GNPs concentration, from 5.8×10 −4 cm 2 V −1 s −1 in pure polymer to a plateau of 2.3×10 −2 cm 2 V −1 s −1 when the GNP concentration ranges between 1.6 % and 3.2 %. These results are consistent with previously described studies on similar composites .…”
Section: Resultsmentioning
confidence: 99%
“…Despite such excellent transport properties, their application as semiconductor in electronics is hampered by the absence of a band gap, which is mandatory to control charge mobility, and it is essential for any logic application . However, composites of OSPs and GNPs can exhibit mutually beneficial effects, as they combine both semiconducting behavior of the polymers and enhanced charge transport characteristics of graphene . A typical demonstration of graphene/organic semiconductor heterojunction was previously realized as a highly photosensitive material due to strong absorption of organic semiconductor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has a limited effect on the capacitance but inevitably serves to increase the electrical conductivity. There are various theories to these ends including the jamming and percolation theories relevant to both magnetorheological fluids and polymer composites . The jamming theory has also been investigated specifically for shear thickening organo‐silicon oxide polymers .…”
Section: Discussionmentioning
confidence: 99%